Pengaruh Kecerdasan dan Literasi Keuangan Terhadap Ketahanan Keuangan UMKM di Sentra Wisata Kuliner Jambangan Surabaya - Alinda Dwi Jofanka; Shofiatus Sa’diyah; Farah Estianingtyas; Maria Yovita R.Pandin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of intelligence and financial literacy on the financial resilience of Micro, Small and Medium Enterprises in the Jambangan Culinary Tourism Center, Surabaya. This research was conducted on the type of business, namely in the culinary or trading business sector with a sample size of 30 micro, small and medium enterprises. In this study using a quantitative approach method. This study uses multiple linear regression techniques for hypothesis analysis. The results of the study show that intelligence and financial literacy have a high impact of 57,1% on the financial resilience of Micro, Small and Medium Enterprises in the Jambangan Culinary Tourism Center, Surabaya.